Hubungan Pengetahuan dan Sikap dengan Partisipasi Pedagang dalam Pengelolaan Sampah di Pasar Labean Kecamatan Balaesang Kabupaten Donggala, Sulawesi Tengah - Purwiningsih, Sri; Sekeon, Robi Adikari; Mua, Estelle Lilian (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
According to Presidential Regulation No. 112 of 2007, a market is an area where goods are bought and sold with more than one seller, whether referred to as a traditional market, shopping center, shops, malls, plazas, trade centers or other names. Waste management in Indonesia is still a problem that has not been handled properly, as in Labean Market. The purpose of this study was to determine the relationship between knowledge and attitudes with trader participation in waste management at Labean Market, Balaesang District, Donggala Regency, Central Sulawesi. The type of research is analytical with a cross-sectional approach. The variables in this study are knowledge and attitudes with trader participation in waste management in the market. The types of data are primary and secondary. Data collection using questionnaires. Data analysis using univariate and bivariate analysis with the Chi-Square test. The population in this study were all traders in the market as many as 105 people. The sample in this study amounted to 32 people. The results of this study indicate that there is a relationship between knowledge and trader participation, with a p-value = 0.013 (p-value ≤ 0.05), trader attitudes and trader participation, with a p-value = 0.046 (p-value ≤ 0.05). The conclusion in this study is that there is a significant relationship between knowledge and trader participation in waste management in the market. There is a significant relationship between attitudes and trader participation in waste management in Labean Market, Balaesang District, Donggala Regency, Central Sulawesi. Suggestions for traders should provide temporary waste storage in kiosks/stalls so that the market head can more easily pick up waste and in terms of aesthetics it also looks good.